Analysis of Web Server Logs to Understand Internet User Behavior and Develop Digital Marketing Strategies - Mowla, Saleh; P. Shetty, Nisha (International Journal of Engineering and Technology, 2018)
With the advancement of technology and widespread availability of information through the internet and the World Wide Web, it has become possible for small-scale industries to convert and expand themselves by increasing awareness and exposure of their businesses. One of the most popular and easiest way to increase a customer base is by creating websites and thus engaging with customers online. However, with the increase in the number of websites and other available source of advertisements, it has become a need to design websites in a way that keeps the customers and viewers engaged and interested so that they return with positive expectations. One way of analyzing website popularity and online customer behavior is by analyzing web server logs with the help of web usage mining techniques to find unknown patterns and generate insights about different aspects of the website. The paper discusses a live scenario where logs of a blogging website have been mined and analyzed to better improve the structure of the site as well as understand the behavior of the viewers who have visited the site. The paper also provides recommendations on improving the structure of the website to adopt effective digital marketing strategies.
Keywords: digital marketing; pattern discovery; server logs; web analytics; web usage mining